SYNTAX ANALYSIS OF ENGLISH NOMINAL PHRASE STRUCTURE AND ITS IMPLICATIONS FOR GRAMMAR LEARNING: EFL LEARNERS - Imelda Kurniati Siregar; Reinasya Br Surbakti; Tiara Adelia; Siti Ismahani (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
This study aims to analyze the structure of English noun phrases and examine their implications for grammar learning for learners of English as a Foreign Language (EFL). The study employs a qualitative approach using a literature study method by reviewing and analyzing books and journal articles that discuss noun phrase structures from a syntactic perspective and common errors made by EFL learners. The analysis focuses on the constituent elements of noun phrases, including the head noun, determiners, pre-modifiers, and post-modifiers. The findings show that EFL learners still experience significant difficulties in constructing correct noun phrases, particularly in the use of determiners, adjective order, and post-modifying structures such as prepositional phrases and relative clauses. The errors identified generally include omission, addition, misformation, and misordering, which are influenced by the complexity of noun phrase structures and interference from the learners’ first language. These errors affect clarity of meaning, grammatical accuracy, and the quality of learners’ academic writing. Therefore, a solid understanding of noun phrase structure is essential to improve learners’ syntactic competence and academic writing ability. This study is expected to contribute to the development of more effective and structure-based grammar teaching strategies for EFL learners. ABSTRAK Penelitian ini bertujuan untuk menganalisis struktur frasa nomina dalam bahasa Inggris serta mengkaji implikasinya terhadap pembelajaran tata bahasa bagi pembelajar bahasa Inggris sebagai bahasa asing (EFL). Penelitian ini menggunakan pendekatan kualitatif dengan metode studi pustaka melalui penelaahan dan analisis buku serta artikel jurnal yang membahas struktur frasa nomina dari perspektif sintaksis dan kesalahan yang umum dilakukan oleh pembelajar EFL. Analisis difokuskan pada unsur-unsur pembentuk frasa nomina yang meliputi unsur inti (head noun), penentu (determiner), pre-modifier, dan post-modifier. Hasil kajian menunjukkan bahwa pembelajar EFL masih mengalami kesulitan yang signifikan dalam membentuk frasa nomina yang benar, khususnya dalam penggunaan determiner, urutan adjektiva, serta struktur post-modifier seperti frasa preposisional dan klausa relatif. Kesalahan yang ditemukan umumnya berupa omission, addition, misformation, dan misordering yang dipengaruhi oleh kompleksitas struktur frasa nomina serta interferensi bahasa pertama pembelajar. Kesalahan-kesalahan tersebut berdampak pada kejelasan makna, ketepatan gramatikal, dan kualitas penulisan akademik pembelajar. Oleh karena itu, pemahaman yang kuat terhadap struktur frasa nomina sangat penting untuk meningkatkan kompetensi sintaksis dan kemampuan menulis akademik pembelajar EFL. Penelitian ini diharapkan dapat berkontribusi pada pengembangan strategi pembelajaran tata bahasa yang lebih efektif dan berbasis struktur.